2011
DOI: 10.1373/clinchem.2011.165662
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values for Aldosterone–Renin Ratios in Normotensive Individuals and Effect of Changes in Dietary Sodium Consumption

Abstract: BACKGROUND Determination of the aldosterone-to-renin ratio (ARR) in blood is the preferred screening test for primary aldosteronism. Renin can be measured as the plasma renin activity (PRA) or the plasma renin concentration (PRC). Consequently, the ARR can be measured either based on the PRA (ARRpra) or based on the PRC (ARRprc). In contrast with the ARRpra, the data on reference values for the ARRprc are limited. Moreover, whether the ARRpra or ARRprc is affected by variations in salt intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 18 publications
4
33
4
Order By: Relevance
“…Similarly, increased sodium can suppress aldosterone secretion, although the effect on the PA/PR ratio is minimal. In a study investigating sodium loading on the PA/PR ratio in normotensive adults, only a 5% reduction in the PA/PR ratio was found after 3 d of high-dose sodium loading [30]. In our patients, serum sodium values were within normal limits at each time point.…”
Section: Discussioncontrasting
confidence: 54%
“…Similarly, increased sodium can suppress aldosterone secretion, although the effect on the PA/PR ratio is minimal. In a study investigating sodium loading on the PA/PR ratio in normotensive adults, only a 5% reduction in the PA/PR ratio was found after 3 d of high-dose sodium loading [30]. In our patients, serum sodium values were within normal limits at each time point.…”
Section: Discussioncontrasting
confidence: 54%
“…Indeed, the clinical observations in the current study reflect this hypothesized pattern by demonstrating higher ARR (renin-independent aldosteronism) with older age, and dysregulated aldosterone physiology (higher SASSI) with older age (failure to adequately suppress aldosterone despite lower PRA with sodium loading and failure to adequately stimulate aldosterone with sodium restriction). Human studies with relatively small sample sizes have previously suggested that older age may be associated with lower aldosterone secretion 11-15 . The present study extends these findings by studying a very large sample size with a wide range in age, and by deemphasizing focus on absolute aldosterone levels and rather focusing on characterizations of aldosterone and renin in relation to their expected or anticipated physiologic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Both angiotensin II (Ang II) and K + increase intracellular calcium signaling as a primary pathway to regulate aldosterone production 5-10 . Prior human studies with small sample sizes have suggested that older individuals may secrete less aldosterone than younger ones 11-15 ; however, the dynamic of aldosterone physiology across the entire age continuum has not been studied in depth. Furthermore, corresponding age-related changes to the adrenal ZG or expression of CYP11B2 have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…This can be verified by checking the 24-h urinary sodium (in patients who are not taking diuretics or fludrocortisone, urinary sodium >100 mEq/24 h indicates salt repletion). For the patient with nOH, it is recommended that they add up to 1–2 teaspoons (2.3–4.6 g) of salt per day to their normal diet [54–56]. Patients at risk for heart failure or severe peripheral edema must be closely monitored for worsening symptoms and salt intake adjusted downward accordingly [43, 57].…”
Section: Treating Nohmentioning
confidence: 99%